Towards Successes in the Management of Nonconvulsive Status Epilepticus: Tracing the Detection-to-Needle Trajectories. Issue 3 (May 2020) - Baang, Hae Young; Swingle, Nicholas; Sajja, Kalyan; Madhavan, Deepak; Shostrom, Valerie K.; Taraschenko, Olga
Abstract : Purpose: Data on the timeliness of emergent medication delivery for nonconvulsive status epilepticus (NCSE) are currently lacking. Methods: Retrospective chart reviews (between 2015 and 2018) and analyses of all patients with NCSE were performed at the University of Nebraska Medical Center, a level 4 epilepsy center, to determine the latencies to order and administration of the first, second, and third antiepileptic drugs (AEDs). Recurrent NCSE cases were considered independently and classified as comatose and noncomatose. Results: There were 77 occurrences of NCSE in 53 patients. The first, second, and third AEDs were delivered with substantial delays at median times of 80 (25%–75% interquartile range, 44–166), 126 (interquartile range, 67–239), and 158 minutes (interquartile range, 89–295), respectively, from seizure detection. The median times to the order of the first and second AEDs were 33 and 134.5 minutes longer in comatose NCSE patients compared with those with noncomatose forms, respectively ( P = 0.001 and 0.004, respectively). The median times between the AED orders and their administration in these two groups were the same ( P = 0.60 and 0.37, respectively). With bivariate analysis, the median latencies to administration of the first, second, and third AEDs were significantly increased by 33, 109.5, and 173 minutes, respectively, in patients who died within 30 days compared with those who survived ( P = 0.047, P = 0.02, P = 0.0007, respectively). Conclusions: The administration of the first, second, and third AEDs for NCSE was delayed. Slow initiation of acute treatment in comatose patients was caused by delays in the placement of the medication order. Abstract : Supplemental Digital Content is Available in the Text.